Pelacakan Titik Daya Maksimum Algoritma Incremental Conductance pada Photovoltaic Dipasang Paralel dan Seri - Matalata, Hendi; Wustha Johar, Leily (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Photovoltaic (PV) is an environmentally friendly renewable energy source. Photovoltaic when connected directly to the load, the power delivered to the load is not optimal. Therefore it is important to get maximum power from the PV system to increase efficiency. This study presents an MPPT system using the Incremental Conductance (IC) algorithm to analyze PV systems installed in parallel and installed in series using 3 PVs. This IC algorithm works by monitoring the current gradient to determine the direction of voltage change and providing a change in derivative voltage so that it can determine the speed of delivery. From the results of the study, the average power using 3 PVs installed in series was 95.4% and using 3 PVs installed in parallel was 88.44%. The algorithm (IC) has a faster response in tracking the maximum power point when installed in parallel even though its efficiency is lower. However, current variations when there are changes in solar radiation tend to be constant as long as the temperature conditions are close to stable.